COMMODITY CHARACTERISTICS OF THE MODERN MEN’S SHOES - SIRENKO, SVITLANA; SHARKO, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The authors determined that the current situation in the market of men’s shoes is developing in accordance with the principles of demand theory. As a result of declining incomes and a significant increase in prices, footwear consumption decreases to the level of minimum needs, consumption of cheap and low-quality goods increases. The authors found that footwear production in Ukraine is declining, despite the "fresh blood" in the form of numerous small workshops that have appeared in the country over the past two years in a wave of fashion for everything Ukrainian, the industry is still in the same state as and the entire economy. Currently, the situation in the country is quite favorable for increasing the production of domestic footwear, as some people are ready to give it preference over imported, for economic or patriotic reasons. But consumers do not have enough information about domestic products, in addition, it is poorly represented in retail outlets in Vinnytsia. In the last few years, the factors by which the Ukrainian consumer decides whether to buy a new pair of shoes, and if so, which one, have changed significantly. First, the main priority was price, not quality. If before the vast majority of consumers bought only leather shoes, now they agree to other materials to save. But Ukrainian manufacturers almost do not make shoes from artificial materials. On the one hand, they are not used to working with them, on the other - they focus on consumer tastes. However, they still do not take into account two important circumstances that have significantly changed consumer tastes in recent times: first, buyers want cheaper products; second, more and more consumers are refusing to wear genuine leather clothing and footwear for ethical reasons. So if manufacturers take into account new changing circumstances and updated consumer demands, they will be able to conquer most of the footwear market without much effort. The paper presents the results of research on the range of modern men’s shoes. A marketing study of the range of footwear of a specific regional market was conducted. The commodity characteristics of some types of modern men’s footwear, in particular "Oxfords", "Derby" are presented.